1997
DOI: 10.1007/s004010050717
|View full text |Cite
|
Sign up to set email alerts
|

Changes in weight and compositions of major membrane components of human brain during the span of adult human life of Swedes

Abstract: Brain weight, total solids, protein, and major lipids have been determined in 83 female and 101 male brains from subjects 20-100 years of age. The brain weight began to diminish at 20 years of age. The brain weight at 20 years for females: 1,368 +/- 26 and for males 1,632 +/- 27 g diminished at 100 years for females to 1,100 +/- 25 and for males to 1,266 +/- 25 g, a decrease of 20% for female and 22% for male brains. The decrease in dry solids was larger during the same period, 36% for females and males. Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
125
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(144 citation statements)
references
References 14 publications
14
125
0
5
Order By: Relevance
“…It is also well known that the brain volume decreases with age in our sample by À113 ml/50 years (8.2%), which is similar to studies based on autopsy (Debakan and Sadowsky, 1978;Miller et al, 1980;Svennerholm et al, 1997) and MRI data (Blatter et al, 1995;Jernigan et al, 2001). This loss is more pronounced in the males than females and in the gray than the white matter compartment.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It is also well known that the brain volume decreases with age in our sample by À113 ml/50 years (8.2%), which is similar to studies based on autopsy (Debakan and Sadowsky, 1978;Miller et al, 1980;Svennerholm et al, 1997) and MRI data (Blatter et al, 1995;Jernigan et al, 2001). This loss is more pronounced in the males than females and in the gray than the white matter compartment.…”
Section: Resultssupporting
confidence: 91%
“…First, autopsy studies have been carried out systematically for more than 100 years now (Blinkov and Glezer, 1968;Chrzanowska and Beben, 1973;Debakan and Sadowsky, 1978;Hwang et al, 1995;Miller et al, 1980;Peters et al, 2000;Svennerholm et al, 1997). Because real volumes and weights are measured, data from autopsy studies may be considered as the ''gold standard''.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to brain shrinkage in senescence (71), the capacity of the brain to produce ATP via oxidative phosphorylation decreases (10) and, in combination with chronic ischemia of white matter (63), this results in a decline of cognitive function. Furthermore, age-related mitochondrial dysfunction has been associated with the neuronal loss, which is a feature of neurodegenerative diseases (13).…”
mentioning
confidence: 99%
“…Brain size and weight reduction occurs mainly in the areas of cerebral cortex. It has been widely found that the volume of the brain and/or its weight declines with age at a rate of around 5% per decade after age 40 [10]. It must be remembered that the brains of an elderly group may show cohort effects related to wider environmental influences, for example, lack of high energy foods while growing up [11].…”
Section: Discussion:-mentioning
confidence: 99%